How do you factor \[2{x^2} + 8x + 8 = 0\]?
Answer
Verified
438.3k+ views
Hint: A polynomial of degree two is called a quadratic polynomial and its zeros can be found using many methods like factorization, completing the square, graphs, quadratic formula etc. The quadratic formula is used when we fail to find the factors of the equation. If factors are difficult to find then we use Sridhar’s formula to find the roots. That is \[x = \dfrac{{ - b \pm \sqrt {{b^2} - 4ac} }}{{2a}}\].
Complete step-by-step solution:
Given, \[2{x^2} + 8x + 8 = 0\]
Since the degree of the equation is 2, we have 2 factors.
On comparing the given equation with the standard quadratic equation\[a{x^2} + bx + c = 0\], we have\[a = 2\], \[b = 8\] and \[c = 8\].
The standard form of the factorization of quadratic equation is \[a{x^2} + {b_1}x + {b_2}x + c = 0\], which satisfies the condition \[{b_1} \times {b_2} = a \times c\] and \[{b_1} + {b_2} = b\].
We can write the given equation as \[2{x^2} + 4x + 4x + 8 = 0\], where \[{b_1} = 4\] and \[{b_2} = 4\]. Also \[{b_1} \times {b_2} = 4 \times 4 = 16(ac)\] and \[{b_1} + {b_2} = 4 + 4 = 8(b)\].
Thus we have,
\[ \Rightarrow 2{x^2} + 8x + 8 = 2{x^2} + 4x + 4x + 8\]
\[ = 2{x^2} + 4x + 4x + 8\]
Taking ‘2x’ common in the first two terms and taking 4 common in the remaining two terms we have,
\[ = 2x\left( {x + 2} \right) + 4(x + 2)\]
Again taking \[\left( {x + 2} \right)\] common we have,
\[ = \left( {x + 2} \right)\left( {x + 2} \right)\]
Hence the factors of \[2{x^2} - 6x + 4 = 0\] are \[\left( {x + 2} \right)\] and \[\left( {x + 2} \right)\].
(We can also find the roots of the given quadratic equation by equating the obtained factors to zero. That is
\[\left( {x + 2} \right)\left( {x + 2} \right) = 0\]
By zero product principle we have,
\[\left( {x + 2} \right) = 0\] or \[\left( {x + 2} \right) = 0\]
\[x = - 2\] or \[x = - 2\]these are the roots)
Note: We can easily solve this if we know some idea of algebraic identity,
\[2{x^2} + 8x + 8 = 0\]
We can divide the whole equation by 2, to make it simple
\[{x^2} + 4x + 4 = 0\]
But we know \[{(a + b)^2} = {a^2} + 2ab + {b^2}\], applying this we have,
\[{(x + 2)^2} = 0\]
Hence the factors of \[2{x^2} - 6x + 4 = 0\] are \[\left( {x + 2} \right)\] and \[\left( {x + 2} \right)\]
These are the roots of the given polynomial of degree 2. In above, if we are unable to expand the middle term of the given equation into a sum of two numbers then we use a quadratic formula to solve the given problem. Quadratic formula and Sridhar’s formula are both the same. Careful in the calculation part.
Complete step-by-step solution:
Given, \[2{x^2} + 8x + 8 = 0\]
Since the degree of the equation is 2, we have 2 factors.
On comparing the given equation with the standard quadratic equation\[a{x^2} + bx + c = 0\], we have\[a = 2\], \[b = 8\] and \[c = 8\].
The standard form of the factorization of quadratic equation is \[a{x^2} + {b_1}x + {b_2}x + c = 0\], which satisfies the condition \[{b_1} \times {b_2} = a \times c\] and \[{b_1} + {b_2} = b\].
We can write the given equation as \[2{x^2} + 4x + 4x + 8 = 0\], where \[{b_1} = 4\] and \[{b_2} = 4\]. Also \[{b_1} \times {b_2} = 4 \times 4 = 16(ac)\] and \[{b_1} + {b_2} = 4 + 4 = 8(b)\].
Thus we have,
\[ \Rightarrow 2{x^2} + 8x + 8 = 2{x^2} + 4x + 4x + 8\]
\[ = 2{x^2} + 4x + 4x + 8\]
Taking ‘2x’ common in the first two terms and taking 4 common in the remaining two terms we have,
\[ = 2x\left( {x + 2} \right) + 4(x + 2)\]
Again taking \[\left( {x + 2} \right)\] common we have,
\[ = \left( {x + 2} \right)\left( {x + 2} \right)\]
Hence the factors of \[2{x^2} - 6x + 4 = 0\] are \[\left( {x + 2} \right)\] and \[\left( {x + 2} \right)\].
(We can also find the roots of the given quadratic equation by equating the obtained factors to zero. That is
\[\left( {x + 2} \right)\left( {x + 2} \right) = 0\]
By zero product principle we have,
\[\left( {x + 2} \right) = 0\] or \[\left( {x + 2} \right) = 0\]
\[x = - 2\] or \[x = - 2\]these are the roots)
Note: We can easily solve this if we know some idea of algebraic identity,
\[2{x^2} + 8x + 8 = 0\]
We can divide the whole equation by 2, to make it simple
\[{x^2} + 4x + 4 = 0\]
But we know \[{(a + b)^2} = {a^2} + 2ab + {b^2}\], applying this we have,
\[{(x + 2)^2} = 0\]
Hence the factors of \[2{x^2} - 6x + 4 = 0\] are \[\left( {x + 2} \right)\] and \[\left( {x + 2} \right)\]
These are the roots of the given polynomial of degree 2. In above, if we are unable to expand the middle term of the given equation into a sum of two numbers then we use a quadratic formula to solve the given problem. Quadratic formula and Sridhar’s formula are both the same. Careful in the calculation part.
Recently Updated Pages
Class 10 Question and Answer - Your Ultimate Solutions Guide
Master Class 11 Business Studies: Engaging Questions & Answers for Success
Master Class 11 Accountancy: Engaging Questions & Answers for Success
Master Class 11 Social Science: Engaging Questions & Answers for Success
Master Class 11 Physics: Engaging Questions & Answers for Success
Master Class 11 Maths: Engaging Questions & Answers for Success
Trending doubts
Assertion The planet Neptune appears blue in colour class 10 social science CBSE
The term disaster is derived from language AGreek BArabic class 10 social science CBSE
Imagine that you have the opportunity to interview class 10 english CBSE
Find the area of the minor segment of a circle of radius class 10 maths CBSE
Differentiate between natural and artificial ecosy class 10 biology CBSE
Fill the blanks with proper collective nouns 1 A of class 10 english CBSE